2009
DOI: 10.1080/13675560903075943
|View full text |Cite
|
Sign up to set email alerts
|

Similarity-based storage allocation rules in an order picking system: an application to the food service industry

Abstract: Today's distribution warehouses often need to process a far higher volume of smaller orders of multiple products which considerably increases logistics costs. They use the so-called order picking (OP) systems where products have to be picked from a set of specific storage locations by an OP process usually driven by production batches or customer orders. The OP is often very labour-intensive and its efficiency largely depends on the distance the order pickers have to travel, which therefore needs to be minimis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 30 publications
2
38
0
5
Order By: Relevance
“…Figure 10 shows the form for setting the assignment of products within the system. Correlated storage assignment rules are supported by the DSS in agreement with the systematic procedure proposed and applied by Bindi et al (2009 and2010). Figure 11 exemplifies the result of the assignment of products within the fast pick area by the use of www.intechopen.com different colours, one for each sku.…”
Section:  Dedicated Storagementioning
confidence: 63%
See 1 more Smart Citation
“…Figure 10 shows the form for setting the assignment of products within the system. Correlated storage assignment rules are supported by the DSS in agreement with the systematic procedure proposed and applied by Bindi et al (2009 and2010). Figure 11 exemplifies the result of the assignment of products within the fast pick area by the use of www.intechopen.com different colours, one for each sku.…”
Section:  Dedicated Storagementioning
confidence: 63%
“…The first set (RANK sku ) i is made of the list of skus ordered in agreement with the application of a ranking criterion (see Figure 10), e.g. the popularity measure based rule or a similarity based & clustering rule (Bindi et al 2009). The second set is made of available locations ordered in agreement with a priority criterion of locations assignment, e.g.…”
Section:  Dedicated Storagementioning
confidence: 99%
“…Thus, worker familiarity with item locations has frequently been cited as a major advantage of dedicated storage assignments (Jane and Laih, 2005;de Koster et al, 2007;Bindi et al, 2009;van Zelst et al, 2009;Chuang et al, 2012), where worker familiarity implies human learning.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…The models adopted in these three hierarchical steps have been illustrated and applied by Bindi et al (2009) and recently by . Even though already discussed in previous studies, we present them briefly in order to make the results reported in the case study more comprehensible:…”
Section: Assignment Sectionmentioning
confidence: 99%
“…In order to group items, the statistical correlation between them should be known or at least be predictable: Frazelle and Sharp (1989) and Brynzér and Johansson (1996) illustrate some examples. Bindi et al (2009) and Manzini et al (2010) have proposed the clustering approach and procedure adopted by this study, building on aspects of the OP problem and the cellular manufacturing (CM) optimisation problem.…”
Section: Storage Assignmentmentioning
confidence: 99%